Advanced Methods for Fabric Hand Digitalization: Enhancing Traceability in Wool Manufacturing (Journal of Fiber Bioengineering and Informatics, 2025)
Fabric hand properties significantly influence consumer satisfaction and product quality in the textileindustry. This study investigates the application of the Fabric Touch Tester (FTT) and Fabric Big Data(FBD) platform for digitising and tracing fabric hand properties during wool textile manufacturing.The research builds on prior studies, confirming that FTT effectively quantifies hand properties duringmanufacturing, while the FBD platform enables real-time visualisation and networked access toproduction data. Results reveal that this approach allows fabric properties during manufacturing tobe well monitored and enable manufacturers to consider whether redundant steps could be eliminatedto enhance resource efficiency. Additionally, this study demonstrates how integrating digital tools intoproduction workflows aligns with ESG and ESPR goals by reducing waste and optimising resourceuse. These findings offer practical guidance for advancing sustainable textile manufacturing, laying thefoundation for more intelligent and transparent production systems.
Keywords: Fabric Touch Tester (FTT); Fabric Hand; Textile Manufacturing; Digitalization; Traceability.